Relationship of Adolescent Reproductive Health Knowledge With Self Adjustments In Puberty Among Boys - Nila Widya Keswara; Sulistyah Sulistyah (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2021)
Puberty is a process of biological changes that include morphology and physiology that occur very rapidly from childhood to adulthood. The purpose of this study was to determine the relationship between adolescent reproductive health knowledge and self-adjustment in puberty among boys at the Marsudisiwi SDK, Malang. An analytical research method was conduct in this research, with a cross sectional approach. Total Sampling technique was use to get 70 samples. Questionnaire instrument with an ordinal scale was used as instrument to drawn data from respondent. Spearman Rank correlation test show p-value value is 0.236. Because the value is 0.236 > 0.05, it can be concluded that H1 is rejected. There is no relationship between knowledge about adolescent reproductive health and adjustment to puberty. The results of this study can be used as a reference for researching with the same variable targeting respondents at a more mature age level (adolescents) related to reproductive health and puberty in boys.